Iraq : Second Review Under the Stand-By Arrangement and Financing Assurances Review-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Iraq. (IMF Staff Country Reports; Country Report ;, 2008)
The second review under Stand-By Arrangement and the financing assurances review highlight Iraq's economic activity and robust growth. The authorities continue to see the improvement in security conditions, and the related recovery of oil and non-oil activity, as a window of opportunity to move toward a path of high and sustainable growth, in the context of continued macroeconomic stability. The Central Bank of Iraq (CBI) is committed to maintaining its tight monetary stance, including through its exchange rate policy.